Radiation monitoring of drinking water in the vicinity of the Beloyarsk NPP - A. V. Panov; A. V. Trapeznikov; A. V. Korzhavin; I. V. Geshel; S. V. Korovin; M. A. Edomskaya (Радиационная гигиена)
The article provides a radiation-hygienic assessment of the current state of drinking water supply sources for the population in the observation area of the the Beloyarsk NPP and the Institute of Nuclear Materials. We determined the content of natural (234U, 238U, 226Ra, 228Ra, 210Po, 222Rn, 210Pb, 228Th, 230Th, 232Th) and technogenic (3H, 14C, 60Co, 90Sr, 134Cs, 137Cs, 238Pu, 239,240Pu, 241Am) radionuclides in drinking water of tap water, water boreholes and water wells in test settlements located at different distances and directions from radiation hazardous facilities. Results of monitoring of water sources in 2012–2013 and 2019 showed the radiation safety of drinking water in the vicinity of the Beloyarsk NPP according to several criteria. Thus, the maximum levels of the gross specific alpha-activity of radionuclides in water samples were 3.9 times lower than the control level (0.2 Bq/kg), the gross specific beta-activity was 5.7 times lower than the control level (1 Bq/ kg). Over the entire observation period, none of the drinking water samples exceeded the control levels both for individual radionuclides and for the sum of the ratios of specific activities to control levels. The content of natural and artificial radionuclides in drinking water near the Beloyarsk NPP decreases in the following order: water wells > water boreholes > tap water. For the past 20 years, there was a decrease in tritium specific activity in drinking water of the Beloyarsk NPP region by 20–35%, depending on the source of water supply. It was noted that the launch of the BN-800 reactor also did not lead to an increase in the content of other artificial radionuclides (90Sr, 137Cs) in groundwater. The average annual effective dose of internal exposure of the population due to drinking water consumption in the vicinity of the Beloyarsk NPP is 0.05 mSv, according to conservative estimates – 0.07 mSv, which is below the radiation safety threshold (0.1 mSv/a) recommended by the WHO. Natural radionuclides play the primary role in the formation of the annual average effective dose for internal irradiation (98.9%) due to drinking water consumption on the considered territories. 210Po makes the largest contribution to the dose from natural radioisotopes – 43%, somewhat less is made by 210Pb – 25%. The third place in the dose formation from natural radionuclides belongs to 234U (8%), 228Ra (7%), 226Ra (6%) and 230Th (6%). The contribution of other natural radioisotopes in the formation of the internal radiation dose from drinking water consumption does not exceed 2-3%. The contribution of technogenic radionuclides to the annual average effective dose from the consumption of drinking water is negligible (about 1%). Of the technogenic components, 90Sr (60%), 3H (20%), and 241Am (12%) play the most significant role in the formation of the internal exposure dose.